2000
DOI: 10.3758/bf03214358
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation, not blocking, in an A+/AX+ flavor-conditioning procedure

Abstract: An A+/AX+ Pavlovian conditioning design typically produces weakened or blocked conditioning to stimulus X. Two experiments were conducted in which rats first received an odor (A+) paired with an emetic US, and then received odor and taste (AX+) paired with the US. In both experiments, the preconditioned odor facilitated conditioning to the taste. In Experiment 1, a group that received two odor-illness pairings in A+ conditioning had a stronger taste aversion than a group that only had a single odor-illness pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
8
28
1
2
Order By: Relevance
“…The first two investigations of augmentation demonstrated the ability of a preconditioned almond odor to augment responding to the bitter taste denatonium saccharide (Batsell & Batson, 1999;Batson & Batsell, 2000) whereas a later report showed that preconditioned denatonium could subsequently augment an almond odor aversion (Batsell, Paschall, Gleason, & Batson, 2001). In almost every respect, the results from these two investigations paralleled each other.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The first two investigations of augmentation demonstrated the ability of a preconditioned almond odor to augment responding to the bitter taste denatonium saccharide (Batsell & Batson, 1999;Batson & Batsell, 2000) whereas a later report showed that preconditioned denatonium could subsequently augment an almond odor aversion (Batsell, Paschall, Gleason, & Batson, 2001). In almost every respect, the results from these two investigations paralleled each other.…”
Section: Introductionmentioning
confidence: 80%
“…For example, in flavor-aversion learning, the pairing of a taste and an odor prior to an illness episode can result in a stronger taste aversion to the weak flavor cue; a phenomenon labeled potentiation (e.g., Rusiniak, Hankins, Garcia, & Brett, 1979). Likewise, when flavor CS A is preconditioned with an illness-producing US, and that preconditioned CS is next conditioned in compound with a new flavor cue (X), the subsequent aversion to X is not blocked, but instead, is augmented (e.g., Batson & Batsell, 2000). It is still unclear why the A+/AX+ conditioning paradigm can yield both competitive and synergistic outcomes, so identification of the mechanisms of the various phenomena may help resolve this question.…”
Section: Introductionmentioning
confidence: 97%
“…That is, responding to a target cue can vary directly with reinforcement of its associate. Examples include potentiation (operationally identical to overshadowing; Rusiniak, Hankins, Garcia, & Brett, 1979), augmentation (operationally identical to blocking; Batson & Batsell, 2000), and second-order conditioning (operationally identical to conditioned inhibition). Moreover, posttraining extinction of the associate (A) can reduce response potential to X following potentiation, augmentation, and second-order conditioning treatments (e.g., Durlach & Rescorla, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, blocking (Kamin, 1968) consists of the weak response that is produced by a CS, X, when it is paired with the US in compound with a second CS, A, which was previously paired with the US on its own. In this case, based on its prior training with the US, CS A is said to block the acquisition or expression of conditioned responding by CS X. Interestingly, some studies have found a contrary effect, that is, a facilitative effect of presenting CS A on responding elicited by CS X, a result known as augmentation (e.g., Batson & Batsell, 2000).…”
Section: Elem (R X )mentioning
confidence: 99%